The evaluation of Persian Thesauri of Health and Biomedical Sciences Based - Hariri, Nadjla; Kazerani, Maryam; Moghaddam Kiya, Reza (Archives of Advances in Biosciences, 2012)
Establishing order, integrity, consistency, and accuracy in thesauri as information storage and retrieval systems plays an important role in the organization of information. The deployment of universally accepted standards, therefore, facilitates the accomplishment of this goal. To achieve this goal, the ANSI /NISO Z 39.19 -2005 standard offers certain rules and principles for constructing controlled vocabularies, including the thesauri, with regard to four dimensions of form construction, semantic relationships, displaying controlled vocabularies, and management systems. These dimensions served as a basis in this study to evaluate the accuracy of vocabulary construction in three Persian Thesauri of Health and Biomedical Sciences, namely, the thesaurus of biological sciences, the thesaurus of health promotion and the thesaurus of medicine. The research method utilized in this study was the analytical survey method. A sampling method was also used to establish samples of the terms contained in the latest edition of every thesaurus. The research instrument used in this study was a checklist defined in Microsoft Excel. The samples for the four dimensions were entered in the checklist and were evaluated on the basis of the relevant standards. The results of the study revealed that the thesauri under study had not given due attention to the standards related to the management dimension. The level of observance of standards for this dimension was only 14% in all of the thesauri. Regarding the dimension of displaying controlled vocabularies, the highest level of observance of the standards was 73% which belonged to the thesaurus of medicine, the lowest level was 54.5% which belonged to the thesaurus of biological sciences, and for the thesaurus of health promotion it was 59%. As for the dimensions of the semantic relations and form construction, the results of the study indicated a higher level of observance of the standards in the thesauri under study. Finally, it was concluded that possessing the required expertise, familiarity with the standards of thesauri construction, utilizing appropriate models, taking the needs of the end users into consideration are among the major factors that if observed could lead to the construction of more effective and efficient thesauri.